The Active Jasmonate JA-Ile Regulates a Specific Subset of Plant Jasmonate-Mediated Resistance to Herbivores in Nature - Schuman, Meredith C.; Meldau, Stefan; Gaquerel, Emmanuel; Diezel, Celia; McGale, Erica; Greenfield, Sara; Baldwin, Ian T. (Frontiers in Plant Science, 2018)
The jasmonate hormones are essential regulators of plant defense against herbivores and include several dozen derivatives of the oxylipin jasmonic acid (JA). Among these, the conjugate jasmonoyl isoleucine (JA-Ile) has been shown to interact directly with the jasmonate co-receptor complex to regulate responses to jasmonate signaling. However, functional studies indicate that some aspects of jasmonate-mediated defense are not regulated by JA-Ile. Thus, it is not clear whether JA-Ile is best characterized as the master jasmonate regulator of defense, or if it regulates more specific aspects. We investigated the function of JA-Ile in the herbivore resistance of the wild tobacco Nicotiana attenuata, a model system for plant-herbivore interactions. We first measured the susceptibility of jasmonate-deficient versus JA-Ile-deficient plants in nature, in comparison to wild-type (WT) controls, and found that JA-Ile-deficient plants (irJAR4xirJAR6) are much better defended even than a mildly jasmonate-deficient line (asLOX3). The differences among lines could be attributed to differences in damage from specific herbivores, which appeared to prefer either one or the other jasmonate-deficient phenotype. We then analyzed the soluble and volatile secondary metabolomes of irJAR4xirJAR6, asLOX3, and WT plants, as well as an RNAi line targeting the jasmonate co-receptor CORONATINE INSENSITIVE 1 (irCOI1), following a standardized herbivory treatment. irJAR4xirJAR6 were the most similar to WT plants, and had a ca. 60% overlap in differentially regulated metabolites with either asLOX3 or irCOI1. In contrast, while at least 25 volatiles differed between irCOI1 or asLOX3 and WT plants, there were no differences in herbivore-induced volatile emission between irJAR4xirJAR6 and WT plants, in glasshouse- or field-collected samples. We further investigated the elicitation of one herbivore-induced volatile known to be jasmonate-regulated and to mediate resistance to herbivores in: (E)-α-bergamotene. We found that JA was a more potent elicitor of (E)-α-bergamotene emission than was JA-Ile, and when treated with JA, irJAR4xirJAR6 plants emitted twenty- to forty-fold more (E)-α-bergamotene than WT. We conclude that JA-Ile regulates specific aspects of herbivore resistance in N. attenuata. This specificity may allow plants flexibility in their responses to herbivores and in managing trade-offs between resistance, versus growth and reproduction, over the course of ontogeny.